Resiliensi Komunitas Kampung Banjar Seminai dalam Menjalankan Program Pengentasan Stunting - Olivia, Yessi; Nizmi, Yusnarida Eka; Yulia, Rahmi; Retnaningsih, Umi Oktyari; Takwa, Tuah Kalti (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
This study aims to analyze how a community manages its resources to address the issue of stunting, which is defined as impaired growth in children due to chronic malnutrition and repeated infections (based on Indonesian Presidential Regulation No. 72 of 2021). Stunting is a serious problem that affects both the physical and psychological development of children. The community studied is Kampung Banjar Seminai, Dayun District, Siak Regency, which claims to have successfully reduced stunting rates in 2023. This is notable because, while the overall stunting rate in Siak Regency slightly increased by 0.33% between 2013 and 2023, the rate in Riau Province dropped significantly from 36.8% to 14% during the same period. The research method involved interviews with people actively involved in tackling stunting at the village level, including the village head, village health workers, and Posyandu volunteers. The results show that the community’s ability to manage resources, along with active participation and good coordination among village actors, played a key role in reducing stunting in Kampung Banjar Seminai. This study highlights the importance of local community involvement in stunting prevention programs and recommends strengthening support and empowering resources at the village level to improve health intervention outcomes.